The long-term effects of maternal deprivation on the number and size of inhibitory interneurons in the rat amygdala and nucleus accumbens - Aleksic, Dubravka; Poleksic, Joko; Agatonovic, Gorana; Djulejic, Vuk; Vulovic, Maja; Aksic, Miljana; Reiss, Gebhard; Hamad, Mohammad I. K.; Jakovcevski, Igor; Aksic, Milan (Frontiers in Neuroscience, 2023)
Introduction There is an increasing evidence supporting the hypothesis that traumatic experiences during early developmental periods might be associated with psychopathology later in life. Maternal deprivation (MD) in rodents has been proposed as an animal model for certain aspects of neuropsychiatric disorders. Methods To determine whether early-life stress leads to changes in GABAergic, inhibitory interneurons in the limbic system structures, specifically the amygdala and nucleus accumbens, 9-day-old Wistar rats were exposed to a 24 h MD. On postnatal day 60 (P60), the rats were sacrificed for morphometric analysis and their brains were compared to the control group. Results Results show that MD affect GABAergic interneurons, leading to the decrease in density and size of the calcium-binding proteins parvalbumin-, calbindin-, and calretinin-expressing interneurons in the amygdala and nucleus accumbens. Discussion This study indicates that early stress in life leads to changes in the number and morphology of the GABAergic, inhibitory interneurons in the amygdala and nucleus accumbens, most probably due to the loss of neurons during postnatal development and it further contributes to understanding the effects of maternal deprivation on brain development.